Design optimization of magneto-rheological damper with improved dispersion stability - Ferdaus, Md Meftahul (Kulliyyah of Engineering, International Islamic University Malaysia, 2015)
Magnetorheological (MR) damper is one of the most advanced applications of semi active damper in controlling vibration. Due to its continuous controllability in both on and off state its practice is increasing day by day in the vehicle suspension system. MR damper's damping force can be controlled by changing the viscosity of its internal magnetorheological fluids (MRF). Still there are some problems with this damper such as MR fluid's sedimentation, optimal design configuration considering all components of the damper, power consumption and temperature rising etc. In this paper both 2-D Axisymmetric and 3-D models of MR Damper are built and finite element analysis is done widely for design optimization. Different configurations of MR damper piston, MR fluid gap, air gap and dampers housing are simulated for comparing the dampers performance variation. From the analytical results it is observed that among different configurations single coil MR damper with linear plastic air gap, top and bottom chamfered piston end and medium MR fluid gap shows better performance than other configurations by maintaining the same input current and piston velocity. Further a prototype MR fluid is developed experimentally where the carbonyl iron particles are coated with xanthan gum to reduce sedimentation and the experimental results are noticeably verifying the improved sedimentation stability. The performance of dampers' containing this new prototype MR fluid are observed by simulation models. Here the outcomes are obviously declaring damper improvement as they are delivering larger damping force compare to the MR damper with conventional fluid. In addition a power saving MR damper model has developed by finite element analysis using ANSYS software, this energy saving MR damper model is obviously showing the solution of damper's temperature rising problem. At last an experimental analysis is performed by using RD-8041-1 MR Damper. These results are compared with the optimized MR Damper's simulation results, which clearly validate the simulated results.